The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep37562
|View full text |Cite
|
Sign up to set email alerts
|

Non-label immune cell state prediction using Raman spectroscopy

Abstract: The acquired immune system, mainly composed of T and B lymphocytes, plays a key role in protecting the host from infection. It is important and technically challenging to identify cell types and their activation status in living and intact immune cells, without staining or killing the cells. Using Raman spectroscopy, we succeeded in discriminating between living T cells and B cells, and visualized the activation status of living T cells without labeling. Although the Raman spectra of T cells and B cells were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 16 publications
(17 reference statements)
1
63
1
Order By: Relevance
“…Further, to sustain the large changes in the nucleus, large numbers of proteins are required in the activated T cells compared with the naive cells. As a result, immune-specific transcription factors upregulating the T cells' surface glycoproteins (17,55,56) show major contributions in the Raman difference spectra apart from Raman peaks of nucleic acids (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, to sustain the large changes in the nucleus, large numbers of proteins are required in the activated T cells compared with the naive cells. As a result, immune-specific transcription factors upregulating the T cells' surface glycoproteins (17,55,56) show major contributions in the Raman difference spectra apart from Raman peaks of nucleic acids (57).…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectra of the tissue have contributions from various splenocytes and can influence the outcome of the PCA-LDA model. It has been previously reported that Raman spectroscopy is capable of differentiating between T cells and B cells (57). Because the tissue areas for Raman mapping were selected randomly, the possibility of uneven distribution of the T cells and B cells within the Raman-mapped area can be foreseen.…”
Section: Discussionmentioning
confidence: 99%
“…That is true for standardized and reproducible expansion of defined immune cell preparations as well as for estimates and methods of measuring specific functionalities of an expanded immune cell population against tumor cells, infections, or inflammations. Moreover, there are also missing generally available methods and techniques for fast and precise measurement of homogeneity of a cell population, of characteristics of sub populations, and single cells [10][11][12][13]. All these aspects appear to be widely responsible for the limited progress by these very promising new therapies.…”
Section: Requirements and Existent Challenges In Producing Immune Celmentioning
confidence: 99%
“…However, the combination of this method with sophisticated software programs with in-depth analyses tools can lead to sharper, high-resolution Raman spectra enabling differentiating looks onto cells enabling subtype identification, quantification, analysis of functional status, etc. [10][11][12][13].…”
Section: Newer Techniques For Characterization and Production Of Immumentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Multivariable analysis, such as principal component analysis (PCA) or a PCA-based approach, called chemometrics in chemistry, is frequently applied to bio-Raman research for visualizing and extracting intrinsic information. [12][13][14][15][16][17][18][19][20][21] This is because bio-Raman data are generally complicated and large, making it almost impossible to interpret the data in an intuitive manner. For example, the number of spectra can easily reach a thousand when the time lapse of cellular differentiation is monitored, which typically takes several days.…”
mentioning
confidence: 99%